The Effect Of Time Management And Work-Life Balance On Job Satisfaction - Fathya Kamila Putri; Sam’un Jasa Raharja; Herwan Abdul Muhyi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The study's title is "The Effect of Time Management and Work-Life Balance on Job Satisfaction". The goal of this research is to determine and comprehend how Time Management and Work-Life Balance affect Job Satisfaction among Generation Z Employees at PT.X. This study employed a quantitative technique. Data was gathered via surveys, literature reviews, and informal interviews. This study's population consisted of Gen Z employees of PT X, who are between the ages of 20 and 27. The research's sample was obtained by a saturation sampling approach, which meant that all populations in the study were utilized as samples. The study included 85 participants as samples. The findings of this study show that Generation Z employees at PT.X had a positive response to time management, that respondents had a positive response to work-life balance, and that time management and work-life balance had a significant effect on satisfaction. This demonstrates how time management and work-life balance are interconnected.